Pride's Nemesis: Nature's Ecological Verdict in The Scarlet Ibis - Rufaida Syifa Rohma; Henrikus Joko Yulianto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This article examines James Hurst’s The Scarlet Ibis through Erik Erikson’s (1950) psychosocial development theory and ecocriticism. It explains how the narrator’s pride, driven by shame, contributes to Doodle’s tragic death. Using a qualitative literary approach with close reading analysis, this study focuses on the narrator’s inner psychological conflict, the sibling relationship, and the symbolic role of nature. The analysis shows that the narrator’s actions change from care to cruelty as shame, ambition, and identity conflict grow stronger, especially during the Initiative vs. Guilt and Industry vs. Inferiority stages. At the same time, natural elements such as the scarlet ibis, the storm, and the swamp work as ecological signs that warn of tragedy and show nature’s moral reaction to human excess. Unlike earlier studies that looked at psychological conflict and environmental symbolism separately, this study combines both perspectives to show how shame between siblings and ecological symbols work together to create the tragic ending. This research adds to ecocritical literary analysis by showing how psychological dynamics can be understood as part of ecological symbols, offering a way to connect individual psychology with environmental meaning in literary study.